WORKING CAPITAL EFFICIENCY, LIQUIDITY, AND SOLVENCY ON PROFITABILITY OF INDONESIAN STATE-PRIVATE BANK - Ridwan Tabe; Olha S. Niode; Jamaluddin Majid (Universitas Islam Negeri Alauddin Makassar, 2023)
Banks are the largest service companies in Indonesia, based on data from the Financial Services Authority, which greatly influences market fluctuations in the services sector. The components used to determine the level of strength and capability of banking institutions include financial ratios related to profitability. This study aims to analyze the efficiency of working capital, liquidity, and solvency on the profitability of Indonesian BUMN (state-owned enterprise) banks. This study was conducted using a quantitative approach. This study employed data from all financial reports published on the website of the Indonesia Stock Exchange and the website of the research object banks. While the sample used was limited to 8 years of financial reports, from 2014 to 2021, the collected data was tested with multiple regression using SPSS v. 25. This study found that working capital efficiency and liquidity did not affect profitability, while solvency did. Furthermore, when analyzed simultaneously, operating capital efficiency, liquidity, and solvency influence profitability.